2023
DOI: 10.3389/fphar.2023.1260599
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics, and safety of ciprofol emulsion in Chinese subjects with normal or impaired renal function

Jun Tao,
Shuaibing Liu,
Ying Ying Zhao
et al.

Abstract: Background: Ciprofol, a novel sedative–hypnotic drug, has been approved for its use in inducing and maintaining general anesthesia, as well as for providing sedation.Methods: In this phase I, single-center, parallel, controlled, open-label clinical trial, our objective was to analyze the pharmacokinetics (PK), pharmacodynamics (PD), and safety of ciprofol emulsion in 24 participants with mild and moderate renal impairment (n = 8 per group) and matched healthy participants (n = 8). An initial loading infusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Phase II clinical trials have demonstrated the pharmacokinetic equivalence of ciprofol to propofol in the induction and maintenance of general anesthesia for elective surgical procedures [1]. Regulatory approval has been granted for ciprofol's use in inducing and maintaining general anesthesia and for providing sedation in intensive care settings [6]. Furthermore, a comprehensive drug-drug interaction study has explored the impact of sodium divalproex on ciprofol in terms of pharmacokinetics and pharmacodynamics [7].…”
Section: Overview Of Ciprofol's Pharmacokineticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phase II clinical trials have demonstrated the pharmacokinetic equivalence of ciprofol to propofol in the induction and maintenance of general anesthesia for elective surgical procedures [1]. Regulatory approval has been granted for ciprofol's use in inducing and maintaining general anesthesia and for providing sedation in intensive care settings [6]. Furthermore, a comprehensive drug-drug interaction study has explored the impact of sodium divalproex on ciprofol in terms of pharmacokinetics and pharmacodynamics [7].…”
Section: Overview Of Ciprofol's Pharmacokineticsmentioning
confidence: 99%
“…Ciprofol, a novel alternative to propofol in clinical intravenous anesthesia, operates primarily by enhancing the ion channel's activity mediated by GABAA receptors [1,5,6]. It functions as a positive allosteric modulator and direct agonist of the GABAA receptor, exhibiting a higher receptor affinity for ciprofol than propofol.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations